ANALISIS FAKTOR–FAKTOR YANG MEMPENGARUHI DIVIDEN KAS PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR PLASTIK DAN KEMASAN YANG TERDAFTAR DI BEI PERIODE 2013-2017 - Crystha Armereo; Nidya Kurniati Putri (Fakultas Ekonomi Universitas Tridinanti Palembang, 2019)
The research was conducted at the Plastic and Packaging Subsector Manufacturing Company listed on the Indonesia Stock Exchange for the 2013-2017 period. This study aims to determine and analyze the effect of free cash flow, fixed asset guarantee, company growth, and the size of the company simultaneously or partially on cash dividends in the plastic and packaging sub-sector manufacturing companies listed on the IDX for the 2013-2017 period. Data in this study were collected with documentation techniques. Documentation techniques are used to obtain data related to this research. Data analysis in this study was conducted with quantitative and qualitative descriptive analysis. Quantitative analysis is used to analyze the classical assumption test, multiple regression, hypothesis testing, and determinant coefficient. The results of this study are: (1) Simultaneously or simultaneously (the results of the statistical test F) shows that there is a positive and significant effect between free cash flow, fixed assets guarantee, company growth, and the size of the company on Cash Dividends in plastic subsector manufacturing companies and packaging listed on the Indonesia Stock Exchange for the 2013-2017 period. (2) Partially (the results of the t-test) show that free cash flow (X1), guarantee of fixed assets (X2), and company size (X4) have a positive and significant effect on Cash Dividend (Y) on plastic subsector manufacturing companies and packaging listed on the Indonesia Stock Exchange for the 2013-2017 period. While the company's growth rate (X3) has no effect on Cash Dividend (Y) on the plastic and packaging sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2013-2017 period. Based on the findings, the next research is to add an independent variable in the research model so that the results of the study can be obtained related to factors that influence cash dividends in more depth, such as ROA, ROE, and others. Keywords: Free:Cash Flow,Guarantee of Fixed Assets,CompanyGrowth, Company Size,Cash Dividen